2005
DOI: 10.2134/jeq2005.0656
|View full text |Cite
|
Sign up to set email alerts
|

Cattle Feedlot Soil Moisture and Manure Content: II. Impact on Escherichia coli O157

Abstract: The moisture and manure contents of soils at cattle feedlot surfaces vary spatiotemporally and likely are important factors in the persistence of Escherichia coli O157 in these soils. The impacts of water content (0.11-1.50 g H2O g(-1) dry feedlot surface material [FSM]) and manure level (5, 25, and 75% dry manure in dry FSM) on E. coli O157:H7 in feedlot soils were evaluated. Generally, E. coli O157:H7 numbers either persisted or increased at all but the lowest moisture levels examined. Manure content modulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
78
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(80 citation statements)
references
References 42 publications
(47 reference statements)
2
78
0
Order By: Relevance
“…Six months after pad use ceased the E. coli counts had dropped by only about an order of magnitude (Table 3). it has been reported that moisture is the most important factor determining bacterial survival (Berry & Miller 2005) which may explain the continued survival. our results suggest that sufficient time should be allowed for pathogens to die-off to low levels prior to land disposal of spent pad materials.…”
Section: Faecal Bacteria In Stand-off Pads and Drainagementioning
confidence: 99%
See 1 more Smart Citation
“…Six months after pad use ceased the E. coli counts had dropped by only about an order of magnitude (Table 3). it has been reported that moisture is the most important factor determining bacterial survival (Berry & Miller 2005) which may explain the continued survival. our results suggest that sufficient time should be allowed for pathogens to die-off to low levels prior to land disposal of spent pad materials.…”
Section: Faecal Bacteria In Stand-off Pads and Drainagementioning
confidence: 99%
“…unlike E. coli, Campylobacter species do not survive well in the environment (Park 2002) and their presence reflects quite recent inputs of contamination. Studies have shown that enteric pathogens decline in stored manures (Hutchison et al 2004b) but that they are seldom completely eliminated , with moisture content being an important factor controlling survival (Berry & Miller 2005). …”
Section: Introductionmentioning
confidence: 99%
“…Flies and other undesirable insects can breed on the manure leading to the health hazards and nuisances associated with them (Lay et al, 2011;Axtell, 1999). Manure is also a source of odor caused by the activity of anaerobic microorganisms in the manure (Berry and Miller, 2005;Fares et al, 2005). It is, therefore, necessary to subject poultry manure to some treatments in order to improve its storage and handling properties and to minimize the risk of disease transmission and environmental pollution.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that moisture levels play a primary role in determining bacterial growth and duration, while temperature was a secondary factor (Berry and Miller, 2005;Collins, 2004;Sinton et al, 2007;Stoddard et al, 1998;Unc and Goss, 2003). Soil physicochemical characteristics including soil type, structure, depth to water tables, and bedrock, i.e.…”
Section: Terrestrial Systems and A Kentucky Studymentioning
confidence: 99%